Niche Partitioning of Labyrinthulomycete Protists Across Sharp Coastal Gradients and Their Putative Relationships With Bacteria and Fungi - Xie, Ningdong; Wang, Zhao; Hunt, Dana E.; Johnson, Zackary I.; He, Yaodong; Wang, Guangyi (Frontiers in Microbiology, 2022)
While planktonic microbes play key roles in the coastal oceans, our understanding of heterotrophic microeukaryotes’ ecology, particularly their spatiotemporal patterns, drivers, and functions remains incomplete. In this study, we focus on a ubiquitous marine fungus-like protistan group, the Labyrinthulomycetes, whose biomass can exceed that of bacterioplankton in coastal oceans but whose ecology is largely unknown. Using quantitative PCR and amplicon sequencing of their 18S rRNA genes, we examine their community variation in repeated five-station transects across the nearshore to offshore surface waters of North Carolina, USA. Their total 18S rRNA gene abundance and phylotype richness decrease significantly from the resource-rich nearshore to the oligotrophic offshore waters, but their Pielou’s community evenness appears to increase offshore. Similar to the bacteria and fungi, the Labyrinthulomycete communities are significantly structured by distance from shore, water temperature, and other environmental factors, suggesting potential niche partitioning. Nevertheless, only several Labyrinthulomycete phylotypes, which belong to aplanochytrids, thraustochytrids, or unclassified Labyrinthulomycetes, are prevalent and correlated with cohesive bacterial communities, while more phylotypes are patchy and often cooccur with fungi. Overall, these results complement previous time-series observations that resolve the Labyrinthulomycetes as persistent and short-blooming ecotypes with distinct seasonal preferences, further revealing their partitioning spatial patterns and multifaceted roles in coastal marine microbial food webs.